External Debt and Growth - Poirson, Helene; Pattillo, Catherine; Ricci, Luca. (Washington, D.C. : International Monetary Fund, 2002)
This paper assesses the non linear impact of external debt on growth using a large panel data set of 93 developing countries over 1969-98. Results are generally robust across different econometric methodologies, regression specifications, and different debt indicators. For a country with average indebtedness, doubling the debt ratio would reduce annual per capita growth by between half and a full percentage point. The differential in per capita growth between countries with external indebtedness (in net present value) below 100 percent of exports and above 300 percent of exports seems to be in excess of 2 percent per annum. For countries that are to benefit from debt reduction under the current HIPC initiative, per capita growth might increase by 1 percentage point, unless constrained by other macroeconomic and structural economic distortions. Our findings also suggest that the average impact of debt becomes negative at about 160-170 percent of exports or 35-40 percent of GDP. The marginal impact of debt starts being negative at about half of these values. High debt appears to reduce growth mainly by lowering the efficiency of investment rather than its volume.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet